Wind in the Silence of Dust - Lavafipur, Ramtin (Lavafipur, Ramtin, 2004)
This experimental documentary visits the sight of massive earthquake that struck the ancient city of Bam in southeast Iran on December 26th, 2003, killing over 40 000 imhabitants and leaving thousands more homeless and destitute.